What are the perceptions about running and knee joint health among the public and healthcare practitioners in Canada? - Esculier, Jean-Francois (PLoS One, 2018)
OBJECTIVES: To evaluate the perceptions of the general public and healthcare practitioners (HCP) in Canada about the relationship between running and knee joint health, and to explore HCP`s usual recommendations to runners with knee osteoarthritis (KOA). METHODS: Non-runners and runners (with and without KOA) and HCP completed an online survey regarding the safety of running for knee joint health. HCP also provided information related to usual clinical recommendations. Proportions of agreement were compared between non-runners and runners. RESULTS: A total of 114 non-runners, 388 runners and 329 HCP completed the survey. Overall, running was perceived as detrimental for the knee joint by 13.1% of the general public, while 25.9% were uncertain. More uncertainty was reported regarding frequent (33.9%) and long-distance (43.6%) running. Statistical analyses revealed greater proportions of non-runners perceiving running negatively compared with runners. Overall, 48.4% believed that running in the presence of KOA would lead to disease progression, while 53.1% believed running would lead to premature arthroplasty. In HCP, 8.2%, 9.1% and 22.2% perceived that running in general, running frequently, or running long-distances are risk factors for KOA, respectively. 37.1% and 2.7% of HCP typically recommended patients with KOA to modify their running training or to quit running, respectively. CONCLUSION: High rates of uncertainty among the general public and HCP in Canada outline the need for further studies about running and knee joint health. Filling knowledge gaps will help inform knowledge translation strategies to better orientate the general public and HCP about the safety of running for knee joint health.